Comparative Analysis of TALE Gene Family in Gramineae - Zicong Liang; Shuai Shi; Baoping Xue; Dongyang Li; Yue Liu; Chang Liu (Agronomy)
The transcription factor known as TALE (three-amino acid loop extension) is essential for plant growth, cell differentiation and responses to environmental stresses. Although the TALE gene family has been identified in various plants, there has been a lack of comprehensive whole-genome identification and analysis in Gramineae species. In this study, 123 TALE family genes were identified in five Gramineae species, which can be categorized into two main subgroups: KONX and BELL. Most of the TALE genes in the same subgroup displayed analogous gene structures and conserved motifs. Furthermore, whole genome duplication (WGD) significantly contributes to the expansion of the TALE gene family in Gramineae. The promoter region of TALE genes in Gramineae contains a large number of cis-elements associated with abiotic stress and hormone response. Tissue-specific expression analysis indicated that most OsTALE, ZmTALE and AtTALE genes were highly expressed in stems and leaves. Additionally, RNA-seq data revealed that OsTALE, ZmTALE and AtTALE genes were found to respond to abiotic stress treatments. Furthermore, we found that the expression levels of SbTALE11/19 were up-regulated in response to PEG and NaCl treatment, respectively. This study provides a significant reference for further research on the biological function of TALE transcription factors in Gramineae plants.